Mental Workload Assessment: The Relationship Between Physiological Heart Rate Variability and Subjective NASA-TLX Measures - Sutarto, Auditya Purwandini; Izzah, Nailul; Kusumawardani, Rahma Indah (The Indonesian Institute of Science and Technology Research, 2024)
The rapid advancement of technology has shifted many jobs to be dominated by mental or cognitive activities. Consequently, it is essential to measure mental workload (MWL) to ensure it does not exceed workers' capacity, which could increase error rates, pose safety risks, reduce productivity, and worsen well-being. This study aims to investigate the relationship between objective and subjective measures of mental workload. Using an experimental approach, HRV physiological signals were recorded from 30 subjects under four different conditions: baseline, MWL test 1 (